Metabolic Inflammation in Inflammatory Bowel Disease: Crosstalk Between Adipose Tissue and Bowel. Issue 2 (February 2015) - Gonçalves, Pedro; Magro, Fernando; Martel, Fátima
Abstract : Abstract: Epidemiological studies show that both the incidence of inflammatory bowel disease (IBD) and the proportion of people with obesity and/or obesity-associated metabolic syndrome increased markedly in developed countries during the past half century. Obesity is also associated with the development of more active IBD and requirement for hospitalization and with a decrease in the time span between diagnosis and surgery. Patients with IBD, especially Crohn's disease, present fat-wrapping or "creeping fat, " which corresponds to ectopic adipose tissue extending from the mesenteric attachment and covering the majority of the small and large intestinal surface. Mesenteric adipose tissue in patients with IBD presents several morphological and functional alterations, e.g., it is more infiltrated with immune cells such as macrophages and T cells. All these lines of evidence clearly show an association between obesity, adipose tissue, and functional bowel disorders. In this review, we will show that the mesenteric adipose tissue and creeping fat are not innocent by standers but actively contribute to the intestinal and systemic inflammatory responses in patients with IBD. More specifically, we will review evidence showing that adipose tissue in IBD is associated with major alterations in the secretion of cytokines and adipokines involved in inflammatory process, in adipose tissue mesenchymal stem cells and adipogenesis, and in the interaction between adipose tissue and other intestinal components (immune, lymphatic, neuroendocrine, and intestinal epithelial systems). Collectively, these studies underline the importance of adipose tissue for the identification of novel therapeutic approaches for IBD. Abstract : Article first published online 22 September 2014.